Grazing on Public Lands - A.Laycock, William; Loper, Dick; Obermiller, Fred W.; Smith, Lamar; Swanson, Sherman R.; Urness, Philip J.; Vavra, Marty (Council for Agricultural Science and Technology (CAST), 1996)
Approximately 262 million acres of public land in the western United States are grazed by domestic livestock. This report discusses and provides scientific information concerning livestock grazing on public lands in the West.
Keywords: Grazing; Public Land; Domestic Livestock